THE CONTEXTUAL TEACHING AND LEARNING MODEL USAGE TO IMPROVE SCIENCE ATTITUDE IN SCIENCE’S LEARNING OF STUDENT CLASS V PUBLIC ELEMENTARY SCHOOL OF MANGKUBUMEN KULON NO. 83 SURAKARTA ACADEMIC YEAR 2017/2018 - Ganing Widarwati; Peduk Rintayati; Chumdari Chumdari (Universitas Sebelas Maret, 2018)
The purpose of this research was to improve science attitude of student class V public elementary school of Mangkubumen Kulon No. 83 Surakarta through the Contextual Teaching and Learning (CTL) model usage in scirnce’s learning. The kind of this research was Classroom Action Research. This research conducted until three cycle with each cycle consist of four stages, namely the planning stage, the stage of action implementation, the observation stage and the reflection stage. The data collection techniques were using interview technique, observation, and document review. The data validity techniques were using triangulation of data sources and triangulation of technique. The data analysis technique was interactive analysis technique which consist of four components, namely data provision, data reduction, data presentation, and data conclusion. The conclude of this research was the CTL model usage could improve the science attitude in science’s learning of student class V public elementary school of Mangkubumen Kulon No. 83 Surakarta academic year 2017/2018.